Environmental, social, and governance (ESG) practice and firm performance: an international evidence - Shaikh, Imlak (Journal of Business Economics and Management, 2022)
This article attempts to bring quantitative evidence of a firm’s sustainability reporting in terms of non-financial voluntary disclosures. The disclosures are made available through the annual report and Corporate Social Responsibility (CSR) and Global Reporting Initiatives (GRI) report. ESG score is a quantitative measure developed and disseminated by Bloomberg, covering about 120 Environmental, Social, and Governance aspects. The study’s research problem is to examine the effects of non-market transnational sustainability strategy on firm performance. The study presents an analysis of nearly 510 firm’s ESG scores across 17 countries for 2010–2018. The descriptive and inductive statistical analysis shows that ESG compliance is more pronounced in European companies. Simultaneously, Asian firms are more disciplined concerning the energy sector, and the Asiapacific counterpart is more inclined toward technology firms. The study shows that GRI and nonGRI companies differ significantly in their accounting performance (ROA and ROE) and market valuations (Tobin’s-Q). The environmental dimension appears intimidating across accounting and market-based firm performance, while the social dimension contributes adversely, and governance positively affects operational efficiency.